1968
DOI: 10.1107/s056774086800364x
|View full text |Cite
|
Sign up to set email alerts
|

The crystal structure of the disodium salt of N-phosphorylcreatine hydrate

Abstract: N-Phosphorylcreatine, a biological 'high energy phosphate', serves as an energy reservoir in vertebrate muscles. Crystals of the disodium salt, Na2PN3C4OsHs.4½H20, were prepared. The space group is P21/c, with unit-cell dimensions a= 24.85, b= 6.64, c= 16.94 A and p= 109.5 o and two formula units per asymmetric unit. If a few weak reflections are ignored, the symmetry is that of the space group C2/c with the same unit-cell dimensions and one formula unit per asymmetric unit. The symmetry of the centered cell w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1978
1978
2014
2014

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…Two hydrate forms, H1 and H2, with water contents of 22.0% and 29.7%, respectively, were disclosed in the literature and can be routinely synthesized using an antisolvent crystallization process with water as a good solvent and ethanol as a poor solvent . The crystal structure of H1 has also been reported in the literature . A primary solid‐state screening experiment revealed that multiple hydrate forms exist when different crystallization methods are applied .…”
Section: Introductionmentioning
confidence: 97%
“…Two hydrate forms, H1 and H2, with water contents of 22.0% and 29.7%, respectively, were disclosed in the literature and can be routinely synthesized using an antisolvent crystallization process with water as a good solvent and ethanol as a poor solvent . The crystal structure of H1 has also been reported in the literature . A primary solid‐state screening experiment revealed that multiple hydrate forms exist when different crystallization methods are applied .…”
Section: Introductionmentioning
confidence: 97%
“…A collapse of the P(6) intermediate ( 11) with ring opening yields a new P(5)' intermediate ( 12) and then the observed acyclic triester (upon enol-keto tautomerization of 13). The ring-opening step 11 - 12 accounts for the effect of imidazole on the unsymmetrical/symmetrical triesters shown in Table IV. Other experimental observations in support of the P(6) intermediate hypothesis have been previously offered.7-26'44 '46 The demonstrated imidazole catalysis of the reaction CEP-OR + R1OH suggests the possibility that imidazole may also catalyze the reaction CEP-IM (6) + ROH ^CEP-OR + IMH; i.e., the latter reaction could be autocatalytic.…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…The molecular structure of cyclophosphamide is known.15 Several other structures relevant to the present investigation have also been solved: sodium phosphoramidate,16 P03NH3Na; calcium 1,3-diphosphorylimidazole hexahydrate,17 Cai.sCsHs^tPOs^Ji^O; diphenyl phosphindimethylamidate,18 (C6H5)2P(0)N(CH3)2, trichlorobis(diethylphenylphosphine)(diethylphenylphosphineiminato)ruthenium(IV),19 and phosphocreatine. 20 The nature of the P-N bond has been discussed in those publications and else- Synthesis of 7,8-Dimethyl-5-methoxy-5-oxo-X5-5-phospha-6-oxaindolizine (la). Methanol (0.51 g, 16 mmol) was added to a solution of lV-(l,2-dimethylethenylenedioxyphosphoryl)pyrrole6 (3; 3.22 g, 16 mmol) in anhydrous CH2CI2 (40 mL) at 20 °C.…”
Section: Cyclophosphamidementioning
confidence: 99%